A Secure Approach for Storing and Using Health Data in a Private Cloud Environment - Pullarao, K.; Thirupathirao, K. (Asian Journal of Science and Applied Technology, 2021)
Cloud computing is an upcoming technology in the field of IT industry. Cost reduction, speed processing, simple accessibility and scalability are the important features of cloud computing. Cloud is robust authentication and more secured technology and it spread in many areas like healthcare sectors in which storing patient information securely more important. The major issues involved in the cloud computing is data confidentiality, data sharing among geographical locations, storing data. This paper provides survey on privacy, security issues and a brief summary about opportunities in cloud. Also it provides a start-up of traditional medical scenario, problems in the current scenario, benefits by adopting cloud in e-health sector and issues arising during adoption of cloud in e-health domain. A methodology of private cloud Iaas is proposed for storing patient and health data in cloud environment.